Influence of Public-Private Partnership Initiative on Financial Assistance and Quality Assurance in Public Secondary Schools in North Central Nigeria - James Salifu Achanya (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study examined the Influence of Public-Private Partnership Initiative on financial assistance and quality assurance in Public Secondary Schools in North Central Nigeria. Specifically, it assessed how PPPI impacts critical areas of school management, including the provision of laboratory equipment and library facilities. The study was guided by two research questions and two corresponding hypotheses, all tested at 0.05 level of significance. A descriptive survey research design was adopted for the study. The population comprised 44,342 teachers across 33 public secondary schools in North-Central Nigeria. Using a multi-stage sampling technique, a sample of 877 respondents was selected. Data were collected through a validated 43-item structured instrument titled Public-Private Partnership Initiative and Management Questionnaire (PPPIMQ). The instrument’s reliability was established with a Cronbach’s alpha coefficient of 0.87, indicating a high level of internal consistency. Descriptive statistics mean and standard deviation were used to answer the research questions, while Chi-square statistics were employed to test the hypotheses at the 0.05 level of significance. The findings revealed that PPPI significantly influenced the management of public secondary schools, particularly in the areas of infrastructure provision, financial assistance and quality assurance. The partnerships were found to bridge funding gaps, enhance transparency and accountability, and improve the overall efficiency of school management. Based on the findings, the study concluded that strengthening PPPI can significantly enhance the quality of public secondary education by ensuring improved learning environments, availability of resources, and enhanced instructional delivery.